Synthesis And Characterization Of Organic-inorganic Bismuth Halide Perovskites For Photonics Applications - Heng, Han Yann (2023)
The study focused on synthesizing organic-inorganic Bi-halides perovskite compounds using different halides (iodide, bromide, and chloride) in a low-toxic and eco-friendly manner. The aim was to develop Pb-free perovskite materials that are less hazardous for workers in the photonics industry and that can be produced using inexpensive and less complicated processes. In this regards, a hydrophobic phenylammonium cation ([(C6H5)NH3]+) was selected, which is known to contributed to a better sample stability. The synthesis methods involved three different approaches: one step solvent (OSS), OSS added oleic acid (OA), and a non-coordinated solvent method at different temperatures. The stability of the samples were evaluated, and it was observed that the ones synthesized at 60 °C exhibited the best stability for most of the solvents and types of halides. The strong ionic interaction between the BiX63- anion and the short short PhA+ cations in the 0D structure greatly contributed to its stability. In general, the PhA4BiCl6 sample showed the highest stability among the halides due to the stronger attraction between nucleus and electron. The study also involved the growth of a single crystal of PhA4BiI6 using a solvent evaporation technique from which the structure of the zero-dimensional (0D) perovskite compounds was determined, supported by field emission scanning electron microscopy with energy-dispersive X-ray (FESEM-EDX) and Fourier transform infrared (FTIR) spectroscopy results